PERAN PEMBINAAN RUMAH KREATIF BUMN BANK BRI CABANG TIMIKA TERHADAP UMKM - Imelda Yanti; Yahya Nusa (Jurnal Ekonomi dan Bisnis, 2025)
The purpose of this study was to determine the development of the BUMN Creative House of Bank BRI Timika Branch on participant businesses so that they have the potential to develop. This study is a descriptive study using a qualitative approach. Based on the results of the analysis, it is known that the development of the BUMN Creative House of Bank BRI Timika Branch has had a very good impact on MSME actors after training, mentoring, and capital assets.